Mindfulness-Based Stress Reduction (MBSR) untuk Manajemen Stres pada Konselor Adiksi - Kusumastuti, Inke -; Westa, I Wayan; Wedastra, I Made (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
Working as an addiction counselor involves specific challenges that might increase one's predisposition to suffering from psychopathology. Therefore, it is paramount for counselors to maintain holistic self-care and self-improvement. The mindfulness approach has good efficacy for improving the wellness of the clinical population, but data regarding its use for health workers, including addiction counselors, are limited. Mindfulness-based stress reduction (MBSR) comprises specific exercise procedures usable for stress management and improving counselors' overall well-being. Related to the notion, other than discussing salient challenges faced by addiction counselors, this paper also discusses how a mindfulness-based approach might be applicable among addiction counselors, added with a brief guide for performing the MBSR.